High-coating-rate cement-based tile adhesive and preparation method thereof

By introducing lightweight fillers and light sand into cement-based tile adhesive and combining it with precise mixing control, the problems of low coating rate and difficult construction are solved, and the preparation of tile adhesive with high coating rate and low cost is achieved.

CN120795810APending Publication Date: 2025-10-17BBMG MORTAR CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511109069.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-08
Publication Date
2025-10-17

AI Technical Summary

Technical Problem

Existing cement-based tile adhesives have low coating rates, high construction resistance, and complex preparation processes, resulting in high costs and making them difficult to promote in the market.

Method used

By using lightweight fillers and light sand combined with moderately heavy fillers, and precisely controlling the component ratios and mixing parameters, a high-coverage cement-based tile adhesive is prepared to reduce bulk density and increase coverage.

Benefits of technology

It significantly improves the coating rate of tile adhesive, reduces the bulk density, makes construction light and labor-saving, ensures the full adhesion rate is qualified, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120795810A_ABST
    Figure CN120795810A_ABST
Patent Text Reader

Abstract

The invention discloses a high-coating-rate cement-based tile adhesive and a preparation method thereof, and mainly relates to the technical field of building materials. The cement-based tile adhesive with the high coating rate comprises the following components: 25.0%-40.0% of cement; 10.0%-25.0% of a light filler; 0%-8.0% of a heavy filler; 0%-50.0% of light sand; 0%-50.0% of heavy sand; 0.20% to 0.40% of cellulose ether; 0%-0.40% of an early strength agent; 0.20%-0.50% of a water reducing agent; 0%-0.40% of wood fiber; 0%-0.06% of starch ether; and 0%-0.01% of an air entraining agent. The light ceramic tile adhesive has the beneficial effects that the technical problems of complex preparation process, high production cost and high material cost of the light ceramic tile adhesive in the prior art are solved, and the technical effects of reducing the stacking density of the ceramic tile adhesive and improving the coating rate are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of building materials, in particular to a high-coating-rate cement-based ceramic tile adhesive and a preparation method thereof. BACKGROUND

[0002] Ceramic tile adhesive is a kind of pre-mixed mortar used for bonding ceramic tiles, stone and other block-shaped decorative materials to substrates. Ceramic tile adhesive is divided into three types according to the cementitious material: cement-based ceramic tile adhesive, paste-like emulsion-based ceramic tile adhesive, and reactive resin ceramic tile adhesive. Cement-based ceramic tile adhesive is the most commonly used ceramic tile adhesive on the market.

[0003] The commonly used cement-based ceramic tile adhesive on the market is a heavy ceramic tile adhesive. The aggregate of the heavy ceramic tile adhesive is usually heavy aggregate such as natural sand or machine-made sand with a bulk density greater than 1400 kg / m 3 . The bulk density of the heavy ceramic tile adhesive is 1300 kg / m 3 ~ 1500 kg / m 3 , the nominal thickening water requirement is 22% ~ 25%, the wet bulk density after water stirring is 1600 kg / m 3 ~ 1700 kg / m 3 , and the coating rate is 70 ~ 80 m

[0004] The preparation method of cement-based ceramic tile adhesive is to mix cement, admixture, graded sand, and additives in a factory to form a dry powder mixture. The production process of cement-based heavy ceramic tile adhesive is very mature. The disadvantages of cement-based heavy ceramic tile adhesive are low coating rate (large unit area dosage) and high resistance during construction kneading, which easily leads to unqualified full adhesion rate. Lightweight aggregate and lightweight filler can be used to prepare lightweight cement-based ceramic tile adhesive. The ceramic tile adhesive in 201210091209.4 "Glass beads with honeycomb and ceramic tile adhesive containing the glass beads" has the characteristics of high volume yield (coating rate) and good workability. However, the lightweight aggregate used in this ceramic tile adhesive costs about 10000 yuan / t, resulting in high cost of the prepared lightweight ceramic tile adhesive, which is difficult to popularize in the market.

[0005] The ceramic tile adhesive in 202210089440.3 "Lightweight ceramic tile adhesive and preparation method thereof" has a bulk density of 600 kg / m 3 ~ 1000 kg / m 3The bulk density of the tile glue can be reduced to half of the original, and the standing time is prolonged and the interfacial bonding strength is improved. In the patent, the light sand (including ceramsite sand and power plant slag sand) needs to be immersed and coated for pretreatment. The process is to uniformly stir the light sand aggregate and wetting liquid (silicone oil) at a speed of 300-600 rpm for 30-60 min. When the light sand aggregate is partially or completely gathered at the bottom of the stirring cylinder, the wetting liquid is optionally discarded, and then the ultra-fine powder is mixed and dispersed to obtain coated light sand. It can be seen that the immersion and coating treatment process is complex and time-consuming, and the coated light sand is an agglomerate with poor fluidity. When the coated light sand is used to prepare light tile glue, the efficiency of ingredient metering, mixing and packaging will be greatly reduced, resulting in a substantial increase in manufacturing cost and a substantial reduction in production efficiency.

[0006] The slag light sand is a light special sand prepared from industrial coal-fired slag through crushing, drying, screening, powder selection and other processes. It has the characteristics of small bulk density, high cylinder pressure strength, heat preservation and heat insulation, sound absorption and noise reduction, and meets the relevant standard requirements in environmental protection performance such as radioactivity and soluble heavy metals. At the same time, slag is an industrial solid waste, and the processing process is simple. The price of slag light sand is moderate. The hollow silica bead is a new type of light aggregate with the characteristics of light weight, high strength, heat insulation, sound insulation, good sphericity and the like.

[0007] Therefore, there is an urgent need to provide a new low-cost high-coating-rate cement-based tile glue and a preparation method thereof. SUMMARY

[0008] The purpose of the present application is to provide a tile glue and a preparation method thereof to alleviate the technical problems of complex preparation process, high production cost and high material cost of light type tile glue in the prior art.

[0009] In order to achieve the above-mentioned purpose of the present application, the following technical solutions are adopted:

[0010] The present application provides a high-coating-rate cement-based tile glue, characterized in that the components include the following components by mass percentage:

[0011] Cement 25.0%-40.0%;

[0012] Light filler 10.0%-25.0%;

[0013] Heavy filler 0%-8.0%;

[0014] Light sand 0%-50.0%;

[0015] Heavy sand 0%-50.0%;

[0016] Cellulose ether 0.20%-0.40%;

[0017] Early strength agent 0%-0.40%;

[0018] water reducing agent 0.20%~0.50%;

[0019] wood fiber 0%~0.40%;

[0020] starch ether 0%~0.06%;

[0021] air entraining agent 0%~0.01%.

[0022] Further, the cement is at least one of Portland cement and Sulphate Aluminate cement; wherein the light filler is at least one of silica fume, metakaolin, fly ash, floating bead, ecological sintered material; the bulk density of the silica fume is 350kg / m 3 ~450kg / m 3 ; the particle size of the metakaolin is above 1000 mesh, and the bulk density is 450kg / m 3 ~550kg / m 3 ; the bulk density of the fly ash is 800kg / m 3 ~950kg / m 3 ; the particle size of the floating bead is 325 mesh, the sieve residue is less than 10%, and the bulk density is 600kg / m 3 ~700kg / m 3 ; the fineness of the ecological sintered material is 45 microns, the sieve residue is ≤30.0%, and the bulk density is 800kg / m 3 ~900kg / m 3 .

[0023] Further, the heavy filler is at least one of heavy calcium, limestone powder and stone powder; the particle size of the heavy calcium is 200 mesh, and the bulk density is 1100kg / m 3 ~1300kg / m 3 .

[0024] Further, the light sand is at least one of slag light sand, polyhollow silica bead, expanded vitrified microbead, expanded perlite, expanded vermiculite and waste rubber particles; the particle size range of the slag light sand is 40 mesh~70 mesh and 70 mesh~140 mesh, the bulk density is 600kg / m 3 ~800kg / m 3 , and the cylinder compressive strength is 3.0MPa~10.0MPa; the particle size range of the polyhollow silica bead is 0.10mm~0.30mm and 0.25mm~0.50mm, and the bulk density is 300kg / m 3 ~450kg / m 3, the barrel pressure intensity is 2.0MPa-3.0MPa; wherein the heavy sand is at least one of natural sand and machine-made sand; the particle size of the heavy sand is 40-70 mesh, 70-140 mesh, and the bulk density is 1200kg / m 3 -1400kg / m 3 . The cellulose ether is at least one of HPMC, HEMC and HEC, and the viscosity of the cellulose ether is 15000mPa·s-100000mPa·s.

[0025] Further, the early strength agent is a calcium salt series early strength agent, preferably calcium formate; wherein the water reducing agent is at least one of polycarboxylic acid water reducing agent, nai series water reducing agent and melamine water reducing agent; wherein the wood fiber is an organic flocculent fiber material obtained by chemical treatment and mechanical processing of natural renewable wood; and wherein the starch ether is a natural macromolecular polyelectrolyte ether that is hydroxymethyl starch and can be dissolved in cold water.

[0026] Further, the air entraining agent is a structure modified air entraining agent, which is obtained by modifying the air entraining agent with a modifier and a structure control agent, and the mass ratio of the modifier to the air entraining agent is 4-8:70-80; wherein the air entraining agent includes at least one of sodium alpha-alkenyl sulfonate, sodium dodecyl sulfate and sodium dodecyl benzene sulfonate; the modifier includes at least one of ethylenediaminetetraacetic acid, sodium citrate, silicone polyether emulsion and hydroxyethyl cellulose; and the structure control agent includes at least one of nano-silicon dioxide or montmorillonite.

[0027] The application provides a preparation method of high-coating-rate cement-based ceramic tile glue, which comprises the following steps: weighing components according to a preset proportion to obtain a set of weighed component materials; respectively placing the set of component materials into a set of feeding tanks, and sequentially taking out a cement feeding tank, a light filler feeding tank and a heavy filler feeding tank in the set of feeding tanks to a mixer for component material feeding in a main glue base feeding stage; based on a mixer monitoring sensor array, monitoring the mixer in a preset monitoring window, and according to a monitoring result and the preset proportion, optimizing feeding and mixing parameters to determine main glue base feeding stage feeding and mixing parameters; based on the main glue base feeding stage feeding and mixing parameters, feedback controlling the mixer, after the main glue base feeding stage is completed, sequentially feeding component materials from a cellulose ether feeding tank, a wood fiber feeding tank, a starch ether feeding tank, an early strength agent feeding tank, a water reducing agent feeding tank and an air entraining agent feeding tank in the set of feeding tanks according to dissolution kinetics, and combining the mixer monitoring sensor array to monitor an additive feeding stage, and according to an additive feeding stage monitoring result, feedback controlling the mixer; after the additive feeding stage is completed, sequentially feeding component materials from a light sand feeding tank and a heavy sand feeding tank in the set of feeding tanks to the mixer, combining the mixer monitoring sensor array to monitor an aggregate uniform distribution stage, and according to an aggregate uniform distribution stage monitoring result, feedback controlling the mixer; after the aggregate uniform distribution stage is completed, obtaining mixed high-coating-rate cement-based ceramic tile glue.

[0028] Further, in a preset monitoring window, based on a mixer monitoring sensor array, monitoring the mixer in a feeding and mixing process, and according to a monitoring result and a preset proportion, optimizing feeding and mixing parameters to determine main glue base feeding stage feeding and mixing parameters, wherein the main glue base feeding stage feeding and mixing parameters include stage feeding and mixing time and stage feeding and mixing speed, which comprises the following steps: extracting the mixer monitoring sensor array to monitor the mixer in a feeding and mixing process to obtain a mixed monitoring data sequence, wherein each mixed monitoring data includes current, feeding speed, material weight and particle distribution uniformity; iteratively analyzing the mixed monitoring data sequence to determine a mixed monitoring iterative trend feature, and taking the mixed monitoring iterative trend feature as a monitoring result; according to a preset feeding and mixing parameter identifier, identifying the monitoring result and the preset proportion to determine initial feeding and mixing parameters; and analyzing the initial feeding and mixing parameters for mixing uniformity, if a mixing uniformity factor is greater than or equal to a preset mixing uniformity factor threshold, taking the initial feeding and mixing parameters as the main glue base feeding stage feeding and mixing parameters.

[0029] Further, the mixed monitoring data sequence is subjected to iterative trend interaction analysis, mixed monitoring iterative trend characteristics are determined, and the mixed monitoring iterative trend characteristics are taken as monitoring results, comprising: trend analysis is performed on the mixed monitoring data sequence by using a first interaction analysis branch and a second interaction analysis branch respectively, and first mixed monitoring iterative trend characteristics and second mixed monitoring iterative trend characteristics are determined, wherein the analysis scale of the first interaction analysis branch is greater than the analysis scale of the second interaction analysis branch; similarity analysis is performed on the first mixed monitoring iterative trend characteristics and the second mixed monitoring iterative trend characteristics, an interaction matrix is constructed, and the first mixed monitoring iterative trend characteristics are enhanced by using the interaction matrix, and the mixed monitoring iterative trend characteristics are obtained.

[0030] Further, if the mixed balance factor is less than a preset mixed balance factor threshold, the initial dosing mixed parameter is adjusted according to a preset adjustment scale, and a stage dosing mixed parameter is obtained; when the mixed balance factor of the stage dosing mixed parameter is greater than or equal to the preset mixed balance factor threshold, the stage dosing mixed parameter is taken as the main glue base dosing stage dosing mixed parameter.

[0031] Compared with the prior art, the present application has the following beneficial effects:

[0032] The present application provides a high-coating-rate cement-based ceramic tile glue, which comprises cement 25.0%-40.0%, light filler 10.0%-25.0%, heavy filler 0%-8.0%, light sand 0%-50.0%, heavy sand 0%-50.0%, cellulose ether 0.20%-0.40%, early strength agent 0%-0.40%, water reducing agent 0.20%-0.50%, wood fiber 0%-0.40%, starch ether 0%-0.06%, and air entraining agent 0%-0.01%. The light sand and light filler with appropriate particle size and strength are introduced, so that the bulk density of the prepared ceramic tile glue is reduced by 25%, the coating rate is increased by 25%, the batch scraping is light during construction, and labor is saved during kneading and pressing, and the full adhesion rate is ensured to be qualified.

[0033] The present invention provides a preparation method of cement-based tile adhesive with high coating rate, which comprises the following steps: weighing each component according to a preset ratio to obtain a weighed component material set, and then placing the component material set into a feeding tank set respectively; in the main adhesive base adding stage, the cement feeding tank, the light filler feeding tank, and the heavy filler feeding tank in the feeding tank set are sequentially called up to add the component materials to a mixer; and then, in a preset monitoring window, the mixer is subjected to feeding and mixing monitoring based on a mixer monitoring sensor array; and the feeding and mixing parameters are optimized according to the monitoring results and the preset ratio, and the feeding and mixing parameters of the main adhesive base adding stage are determined; and then, the mixer is feedback-controlled based on the feeding and mixing parameters of the main adhesive base adding stage. When the main adhesive base adding stage is completed, Afterwards, the cellulose ether feeding tank, wood fiber feeding tank, starch ether feeding tank, early strength agent feeding tank, water reducer feeding tank, and air entraining agent feeding tank in the feeding tank collection are transferred to sequentially add component materials according to dissolution kinetics, and the additive addition stage is monitored in conjunction with the mixer monitoring sensor array. The mixer is feedback-controlled based on the monitoring results of the additive addition stage. When the additive addition stage is completed, the light sand feeding tank and heavy sand feeding tank in the feeding tank collection are transferred to sequentially add component materials to the mixer, and the aggregate uniform distribution stage is monitored in conjunction with the mixer monitoring sensor array. The mixer is feedback-controlled based on the monitoring results of the aggregate uniform distribution stage. When the aggregate uniform distribution stage is completed, a mixed high-coating rate cement-based tile adhesive is obtained. This achieves the technical effect of performing mixing monitoring during the preparation process of the high-coating rate cement-based tile adhesive, improving mixing reliability, and improving preparation quality. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Attachment Figure 1 The present invention provides a flow chart of a method for preparing a high-coverage cement-based tile adhesive.

[0035] Attachment Figure 2 The present invention provides a method for preparing a high-coverage cement-based tile adhesive according to an embodiment of the present invention, which is a flow chart showing the steps of determining the mixing parameters of the main adhesive base during the addition stage.

[0036] Attachment Figure 3 It is a flow chart of obtaining the mixing monitoring iterative trend characteristics in a method for preparing a high-coating-rate cement-based tile adhesive provided by an embodiment of the present invention. DETAILED DESCRIPTION

[0037] The embodiments of the present invention will be described in detail below with reference to the examples. However, it will be understood by those skilled in the art that the following examples are intended only to illustrate the present invention and are not to be construed as limiting the scope of the present invention. Where specific conditions are not specified in the examples, the procedures were carried out according to conventional conditions or the conditions recommended by the manufacturer.

[0038] The application provides high-coating-rate cement-based ceramic tile glue, characterized by comprising the following components in percentage by mass:

[0039] cement 25.0%-40.0%; light filler 10.0%-25.0%; heavy filler 0%-8.0%; light sand 0%-50.0%; heavy sand 0%-50.0%; cellulose ether 0.20%-0.40%; early strength agent 0%-0.40%; water reducing agent 0.20%-0.50%; wood fiber 0%-0.40%; starch ether 0%-0.06%; air entraining agent 0%-0.01%.

[0040] The application significantly reduces the bulk density of high-coating-rate cement-based ceramic tile glue by using light components such as light sand and light filler. The cement, which is inorganic cementitious material and the key to the strength and bonding performance of the ceramic tile glue, is in a content range of 25.0%-40.0%, which ensures the bonding performance and avoids the increase of material cost and construction difficulty. The light filler is used to improve the construction performance and coating rate of the ceramic tile glue, reduce the product density, improve the product coating area and improve the cost performance, and the addition amount is 10.0%-25.0%. The heavy filler is an optional component, and the addition amount is 0%-8.0%, which is used to balance the product density, cost and construction performance. The light sand and heavy sand are optional aggregates, which are used to adjust the slurry consistency, construction performance and structural strength, and the use ranges are 0%-50.0% respectively. The cellulose ether, as a water-retaining thickening agent, is in an addition amount of 0.20%-0.40%, which is used to improve the water retention, anti-sagging performance and smooth construction performance of the ceramic tile glue. The early strength agent is in an amount of 0%-0.40%, which can effectively improve the initial strength and shorten the construction cycle, and is especially suitable for low-temperature environments or fast construction occasions. The water reducing agent is added in an amount of 0.20%-0.50%, which can improve the fluidity and workability of the ceramic tile glue, reduce the water consumption and improve the strength development efficiency. The wood fiber is in an amount of 0%-0.40%, which can increase the crack resistance, flexibility and shear strength of the ceramic tile glue, and is helpful to improve the construction thickness and maintain stability. The starch ether is a modifier, and the addition amount is 0%-0.06%, which is helpful to improve the construction feel, open time and coating smoothness of the ceramic tile glue. The air entraining agent is an optional additive component, and the addition amount is 0%-0.01%, which is used to adjust the density of the glue and improve the water retention and reduce the overall weight. The modified air entraining agent generates a large number of small, stable and suspended bubbles in the high-coating-rate cement-based ceramic tile glue during the stirring process. The wet density of the high-coating-rate cement-based ceramic tile glue is reduced, the coating rate is increased, the elastic modulus is reduced, the full adhesion rate in the paving process is improved, the safety factor and bonding strength after paving are improved, and the process of paving rock plates is facilitated.

[0041] In a preferred embodiment of the application, the cement is at least one of Portland cement and sulphoaluminate cement.

[0042] The light filler is at least one of silica fume, metakaolin, fly ash, floating bead, and ecological sintered material.

[0043] The bulk density of the silica fume is 350kg / m 3 450kg / m 3 .

[0044] The particle size of the metakaolin is 1000 mesh or more, and the bulk density is 450kg / m 3 550kg / m 3 .

[0045] The bulk density of the fly ash is 800kg / m 3 950kg / m 3 .

[0046] The particle size of the floating bead is 325 mesh, the sieve residue is less than 10%, and the bulk density is 600kg / m 3 700kg / m 3 .

[0047] The fineness of the ecological sintered material is 45 microns, the sieve residue is less than or equal to 30.0%, and the bulk density is 800kg / m 3 900kg / m 3 .

[0048] It should be noted that the mesh reflects the ability of the particles to pass through the standard screen, and when the mesh number is larger, the corresponding particles are also finer. The mesh number of the screen is roughly inversely proportional to the corresponding pore size, therefore, the particle size of 1000 mesh or more means that the particle size is less than about 15 microns, which belongs to the category of superfine powder. The bulk density refers to the mass per unit volume of the powder in a natural state (without external force compaction), which is usually expressed in kg / m 3 . The bulk density is not only affected by the density of the particles themselves, but also related to the morphology, particle size distribution, surface roughness and packing structure of the particles. The finer the particles, the more uniform the distribution, and the more regular the shape, the lower the bulk density. In the present application, metakaolin with a bulk density of 450kg / m 3 550kg / m 3 is preferably selected, which can effectively improve the workability and stability of the ceramic tile glue while taking into account light filling and good dispersion performance, and avoid the system from causing coating rate to decrease due to too high particle density or causing sagging and strength loss due to too low particle density.

[0049] The sieve residue is one of the important indicators for measuring the particle size distribution of the powder material, which refers to the percentage of the mass that is retained on the screen during the standard screening experiment. The higher the sieve residue, the more large particles in the material; the lower the sieve residue, the finer or more concentrated the particle size distribution.

[0050] In a preferred embodiment of the present application, the heavy filler is at least one of heavy calcium carbonate, limestone powder, and stone powder;

[0051] The particle size of the heavy calcium carbonate is 200 mesh, and the bulk density is 1100 kg / m 3 ~ 1300 kg / m 3 .

[0052] In a preferred embodiment of the present application, the light sand is at least one of furnace slag light sand, polyhollow silica beads, expanded vitrified microbeads, expanded perlite, expanded vermiculite, and waste rubber particles;

[0053] The particle size of the furnace slag light sand ranges from 40 mesh to 70 mesh and from 70 mesh to 140 mesh, and the bulk density is 600 kg / m 3 ~ 800 kg / m 3 , and the cylinder compressive strength is 3.0 MPa to 10.0 MPa;

[0054] The particle size of the polyhollow silica beads ranges from 0.10 mm to 0.30 mm and from 0.25 mm to 0.50 mm, and the bulk density is 300 kg / m 3 ~ 450 kg / m 3 , and the cylinder compressive strength is 2.0 MPa to 3.0 MPa;

[0055] The heavy sand is at least one of natural sand and machine-made sand;

[0056] The particle size of the heavy sand ranges from 40 mesh to 70 mesh and from 70 mesh to 140 mesh, and the bulk density is 1200 kg / m 3 ~ 1400 kg / m 3 .

[0057] The cellulose ether is at least one of HPMC, HEMC, and HEC, and the viscosity of the cellulose ether is 15000 mPa·s to 100000 mPa·s.

[0058] In a preferred embodiment of the present application, the early strength agent is a calcium salt series early strength agent, preferably calcium formate;

[0059] The water reducing agent is at least one of a polycarboxylic acid water reducing agent, a naphthalene series water reducing agent, and a melamine water reducing agent;

[0060] The wood fiber is an organic flocculent fiber material obtained by chemical treatment and mechanical processing of natural renewable wood;

[0061] The starch ether is a natural high molecular polyelectrolyte ether of hydroxymethyl starch and is soluble in cold water.

[0062] In a preferred embodiment of the present application, the air entraining agent is a structure modified air entraining agent, which is obtained by modifying the air entraining agent with a modifier and a structure regulator, and the mass ratio of the modifier to the air entraining agent is 4-8:70-80.

[0063] For example, the mass ratio of the modifier to the air entraining agent can be 4:90, 5:85, 5:80, 7.5:75, 7.5:70, 5:65, 5:70, 6:75, etc.

[0064] The air entraining agent includes at least one of sodium alpha-alkenyl sulfonate, sodium dodecyl sulfate, and sodium dodecyl benzene sulfonate.

[0065] The modifier includes at least one of ethylenediamine tetraacetic acid, sodium citrate, silicone polyether emulsion, and hydroxyethyl cellulose.

[0066] The structure regulator includes at least one of nano-silicon dioxide or montmorillonite.

[0067] That is, the present application selects at least one of ethylenediamine tetraacetic acid, sodium citrate, silicone polyether emulsion, and hydroxyethyl cellulose as a modifier to be compounded with at least one of sodium alpha-alkenyl sulfonate, sodium dodecyl sulfate, and sodium dodecyl benzene sulfonate to obtain a modified air entraining agent, and selects at least one of silicon dioxide or montmorillonite as a structure regulator to process the modified air entraining agent to obtain a structure modified air entraining agent. The modified structure modified air entraining agent generates small, stable, and suspended air bubbles in the high-coating-rate cement-based ceramic tile adhesive during the stirring process after adding water, so as to reduce the wet density of the high-coating-rate cement-based ceramic tile adhesive, increase the coating rate, reduce the elastic modulus, facilitate the soft pressure in the engineering construction application, improve the full adhesion rate in the paving process of the rock plate, and improve the safety factor and the bonding strength after paving.

[0068] Further, the raw material of the modified air entraining agent includes the modifier and the air entraining agent with a mass ratio of 1-10:60-90.

[0069] The raw material of the structure modified air entraining agent includes the structure regulator and the modified air entraining agent with a mass ratio of 0.2-2:10.

[0070] Further, the mass ratio of the structure regulator to the modified air entraining agent is 0.4-0.8:10, for example, 0.4:10, 0.45:10, 0.5:10, 0.55:10, 0.6:10, 0.65:10, 0.7:10, 0.75:10, 0.8:10, etc.

[0071] In a possible embodiment, the preparation method of the structure modified air entraining agent includes the following steps:

[0072] A liquid modifier and an air-entraining agent liquid are mixed uniformly in a first ratio and powdered to obtain a modified air-entraining agent. A structure control agent is added to the modified air-entraining agent liquid in a second ratio, mixed uniformly, and powdered to obtain a structure-modified air-entraining agent. The first ratio and the second ratio are respectively predetermined by a person skilled in the art.

[0073] The high coating rate cement-based tile adhesive of the present invention has the characteristics of light construction, low density and high bonding strength. The bulk density of the cement-based heavy-duty tile adhesive is 1300kg / m 3 ~1500kg / m 3 , wet density is 1600kg / m 3 ~1700kg / m 3 The bulk density of the high coating rate cement-based tile adhesive of the present invention is 800kg / m 3 ~1000kg / m 3 , wet density is 820kg / m 3 ~1200kg / m 3 The bulk density and wet density of high coverage cement-based tile adhesive are significantly lower than those of heavy-duty cement-based tile adhesive.

[0074] According to the calculation of the paving area, assuming that the construction thickness of cement-based tile adhesive is 1cm, theoretically, the paving area of ​​cement-based heavy-duty tile adhesive per ton is about 75m 3 The lightweight cement-based adhesive of the present invention can cover an area of ​​about 150m per ton. 3 The paving area is significantly higher than that of cement-based heavy-duty tile adhesive. The consumption of the high-coating-rate cement-based tile adhesive of the present invention is about 50% of that of cement-based heavy-duty tile adhesive, which greatly reduces the material consumption per square meter in tile paving construction.

[0075] As attached Figure 1 As shown, the present invention provides a method for preparing a cement-based tile adhesive with a high coating rate, wherein the method comprises:

[0076] Step A100: Weighing each component according to a preset ratio to obtain a set of weighed component materials;

[0077] In one possible embodiment, the preset ratio is the mass ratio of each component, including cement, lightweight filler, heavy filler, aggregate (light sand, heavy sand), additives (such as cellulose ether, water reducer, etc.), predetermined by a person skilled in the art based on target performance (such as bond strength, coating rate, and workability). Weighing refers to the measurement and weighing of each component raw material, typically achieved through precise control using an automated weighing system. The component material collection is a collection of multiple types of materials obtained after weighing, preparing for subsequent staged feeding.

[0078] According to the preset material ratio, for example, the preset ratio of each component material is: ordinary Portland cement 250g, fly ash 100g, silica fume 30g, floating bead 20g, limestone powder 50g, slag light sand (40-70) 200g, slag light sand (70-140) 200g, tailings sand (40-70) 100g, waste rubber particles 20g, redispersible latex powder (vinyl acetate / ethylene copolymer) 20g, cellulose ether (HPMC) 3.0g, calcium formate 5.0g, polycarboxylic acid water reducer 2.0g, wood fiber 2g, starch ether 0.5g, air entraining agent 0.1g. Reliable weighing is carried out by using a high-precision automatic weighing system and setting an error checking mechanism.

[0079] Step A200: The component material set is respectively put into the set of feeding tanks, and in the main glue base adding stage, the cement feeding tank, the light filler feeding tank and the heavy filler feeding tank in the set of feeding tanks are sequentially taken out to add the component materials to the mixer;

[0080] In one embodiment, the set of feeding tanks refers to a plurality of independent tanks or warehouses for temporarily storing different types of materials, which are usually partitioned according to the types of components, such as cement feeding tank, light filler feeding tank, etc., to support subsequent automation and staged feeding. The main glue base adding stage refers to the stage in which the core components (such as cementitious materials and fillers) constituting the tile glue base structure are preferentially added to the mixer.

[0081] The weighed component materials are respectively loaded into the corresponding feeding tanks, and in the main glue base adding stage, the materials are sequentially extracted from the cement, light filler and heavy filler feeding tanks and delivered to the mixer for preliminary mixing. By sequentially adding, the cementitious core can be mixed first to ensure uniform dispersion and improve the initial bonding strength, laying a structural foundation for the gradual cooperation of subsequent additives or aggregates, and achieving the technical effect of avoiding quality defects such as stratification and agglomeration.

[0082] Step A300: In a preset monitoring window, the mixer is monitored based on the mixer monitoring sensor array, and the mixing parameters in the main glue base adding stage are optimized according to the monitoring results and the preset ratio;

[0083] In one possible embodiment, the preset monitoring window is a monitoring time period preset by a person skilled in the art, which can be 3s, 5s, etc. The mixer monitoring sensor array at least includes: a current / torque sensor, a flow meter, a load sensor, and a photoelectric particle sensing module. By using the mixer monitoring sensor array to monitor the addition mixing of the mixer within the preset monitoring window, the mixing condition of the mixer can be grasped, thereby providing data support for subsequent addition mixing parameter optimization in combination with the preset proportioning.

[0084] Step A400: feedback control of the mixer based on the main glue base addition mixing parameter, when the main glue base addition stage is completed, the cellulose ether feeding tank, the wood fiber feeding tank, the starch ether feeding tank, the early strength agent feeding tank, the water reducing agent feeding tank, and the air entraining agent feeding tank in the feeding tank set are sequentially used for component material addition according to dissolution kinetics, and the additive addition stage monitoring is performed in combination with the mixer monitoring sensor array, and feedback control of the mixer is performed according to the additive addition stage monitoring result;

[0085] Step A500: when the additive addition stage is completed, the light sand feeding tank and the heavy sand feeding tank in the feeding tank set are sequentially used for component material addition to the mixer, and the aggregate uniform distribution stage monitoring is performed in combination with the mixer monitoring sensor array, and feedback control of the mixer is performed according to the aggregate uniform distribution stage monitoring result;

[0086] Step A600: when the aggregate uniform distribution stage is completed, a high-coated-rate cement-based ceramic tile adhesive is obtained.

[0087] In one possible embodiment, the preset monitoring window is a monitoring time period preset by a person skilled in the art, which can be 3s, 5s, etc. The mixer monitoring sensor array at least includes: a current / torque sensor, a flow meter, a load sensor, and a photoelectric particle sensing module. By using the mixer monitoring sensor array to monitor the addition mixing of the mixer within the preset monitoring window, the mixing condition of the mixer can be grasped, thereby providing data support for subsequent addition mixing parameter optimization in combination with the preset proportioning.

[0088] The light sand and heavy sand feeding tanks are retrieved, and the low-density light sand is first fed, and then the high-density heavy sand is fed according to the aggregate structure design principle, which is helpful to the full and uniform distribution of the aggregate in the mixing system. The sensor array detects the particle distribution state in real time, such as identifying the distribution uniformity through image processing or reflecting the shear resistance through the current change trend. If the monitoring result does not reach the set standard, the stirring speed or the uniform distribution time is adjusted until the homogeneous, non-piled and non-agglomerated particle structure is formed. This stage plays a decisive role in the workability (such as the scraping feeling and the anti-sliding property) and the physical properties (such as the strength and the coating rate) of the final ceramic tile glue, and is the key link of structure forming in the whole preparation process.

[0089] In one embodiment, the additive feeding stage monitoring is performed in combination with the mixing machine monitoring sensor array based on the same principle as that of determining the main glue base feeding stage feeding mixing parameters, and the feedback control of the mixing machine is performed according to the additive feeding stage monitoring result, and the aggregate uniform distribution stage monitoring is performed in combination with the mixing machine monitoring sensor array, and the feedback control of the mixing machine is performed according to the aggregate uniform distribution stage monitoring result.

[0090] Further, as shown in the pre-set monitoring window, the mixing machine is monitored for feeding mixing based on the mixing machine monitoring sensor array, the feeding mixing parameters are optimized according to the monitoring result and the pre-set ratio, and the main glue base feeding stage feeding mixing parameters are determined, wherein the main glue base feeding stage feeding mixing parameters include the stage feeding mixing time and the stage feeding mixing speed, and the embodiment step A300 further includes: Figure 2

[0091] Step A310: The mixing machine is monitored for feeding mixing by the mixing machine monitoring sensor array to obtain a sequence of mixing monitoring data, wherein each mixing monitoring data includes current, feeding speed, material weight and particle distribution uniformity;

[0092] Step A320: The sequence of mixing monitoring data is iteratively and interactively analyzed to determine the mixing monitoring iterative trend characteristics, and the mixing monitoring iterative trend characteristics are taken as the monitoring result;

[0093] Step A330: The monitoring result and the pre-set ratio are identified according to the pre-set feeding mixing parameter identifier to determine the initial feeding mixing parameters;

[0094] Step A340: The initial feeding mixing parameters are analyzed for mixing uniformity, and if the mixing uniformity factor is greater than or equal to the pre-set mixing uniformity factor threshold, the initial feeding mixing parameters are taken as the main glue base feeding stage feeding mixing parameters.

[0095] Further, as shown in the pre-set monitoring window, the mixing machine is monitored for feeding mixing based on the mixing machine monitoring sensor array, the feeding mixing parameters are optimized according to the monitoring result and the pre-set ratio, and the main glue base feeding stage feeding mixing parameters are determined, wherein the main glue base feeding stage feeding mixing parameters include the stage feeding mixing time and the stage feeding mixing speed, and the embodiment step A300 further includes: Figure 3 ​As shown, the mixed monitoring data sequence is subjected to iterative trend interaction analysis to determine a mixed monitoring iterative trend feature, and the mixed monitoring iterative trend feature is taken as a monitoring result. The step A320 further includes the following steps.

[0096] Step A320-1: The mixed monitoring data sequence is subjected to trend analysis by using a first interaction analysis branch and a second interaction analysis branch respectively to determine a first mixed monitoring iterative trend feature and a second mixed monitoring iterative trend feature, wherein the analysis scale of the first interaction analysis branch is greater than the analysis scale of the second interaction analysis branch.

[0097] Step 320-2: Similar analysis is performed on the first mixed monitoring iterative trend feature and the second mixed monitoring iterative trend feature to construct an interaction matrix, and the first mixed monitoring iterative trend feature is enhanced by using the interaction matrix to obtain the mixed monitoring iterative trend feature.

[0098] Further, if the mixed balance factor is less than a preset mixed balance factor threshold, the initial addition mixed parameter is adjusted according to a preset adjustment scale to obtain a stage addition mixed parameter. When the mixed balance factor of the stage addition mixed parameter is greater than or equal to the preset mixed balance factor threshold, the stage addition mixed parameter is taken as the main rubber base stage addition mixed parameter.

[0099] In one possible embodiment, the mixed monitoring data sequence refers to a series of mixed related data collected in time sequence within a monitoring period, which is used for subsequent trend analysis and state determination. Each mixed monitoring data includes current, addition speed, material weight, and particle distribution uniformity. The current reflects the size of the mixing resistance, the addition speed represents the feeding rhythm of different materials, the material weight is used to monitor whether the set ratio is completed for each stage addition, and the particle distribution uniformity is used to measure the mixing state. All collected values are combined in chronological order to form a complete mixed monitoring data sequence. The data sequence not only objectively reflects the current mixing quality, but also provides a solid data basis for subsequent trend identification, parameter optimization, and dynamic control.

[0100] In one embodiment, the mixed monitoring data sequence is analyzed by using two different analysis scales in two dimensions to obtain a first mixed monitoring iterative trend feature and a second mixed monitoring iterative trend feature. The first interaction analysis branch and the second interaction analysis branch are two analysis channels for trend analysis of the mixed monitoring data sequence, which are respectively based on different analysis scales. The first interaction analysis branch is used to process large time span or low frequency data to grasp the macro trend; and the second interaction analysis branch is used to process short period or high frequency data to capture local anomalies or fluctuations.

[0101] The first interaction analysis branch evaluates the overall mixing trend from a macroscopic perspective (e.g., whether the overall current decreases smoothly, whether the total weight change is linear); the second interaction analysis branch focuses on local changes (e.g., whether the particle distribution is suddenly uneven in a small time period, whether the addition speed is disturbed). The first mixing monitoring iterative trend feature and the second mixing monitoring iterative trend feature are extracted respectively.

[0102] The similarity of the same type of features in the first mixing monitoring iterative trend feature and the second mixing monitoring iterative trend feature is calculated using a cosine function, and the calculation result is normalized. The processing result is filled into an initially empty matrix to construct an interaction matrix of the two features. The interaction matrix is used to measure the synchronization or complementarity of the changes. Through graph convolution network convolution operation of the interaction matrix and the first mixing monitoring iterative trend feature, the long-term trend is corrected in combination with the short-term disturbance signal, and finally a more comprehensive and stable mixing monitoring iterative trend feature is obtained. The mixing monitoring iterative trend feature provides accurate feedback for subsequent addition parameter adjustment.

[0103] A plurality of sample monitoring results, a plurality of sample preset proportions, and a plurality of initial addition mixing parameters are obtained as training data. The neural network is trained in a supervised learning manner, that is, the monitoring results and the proportions are taken as inputs, and the initial addition mixing parameters under known successful experience are taken as label outputs. In the training process, mean square error (MSE) or cross-entropy is used as a loss function to correct the network weight through back propagation, and the weight is updated by combining gradient descent or Adam optimizer until the loss function converges, the error is controlled within a preset threshold, and the model performance is stable. In actual training, for example, more than 30 batches of real mixing process data can be collected as sample data sets. 80% of the samples are used for training, and 20% of the samples are used for verification. The training results show that the difference between the initial addition mixing parameters predicted by the model and the artificial experience parameters is not more than ±5% in 95% of the cases, showing good generalization ability and control precision. The preset addition mixing parameter identifier can quickly output the initial control parameters suitable for the current mixing state according to the real-time monitoring data and product proportions, significantly improving the automation level and the mixing process response ability, and providing reliable input for the next mixing uniformity analysis.

[0104] In one possible embodiment, the initial dosing mixing parameters are analyzed for mixing uniformity in actual operation, i.e., whether the mixing process reaches the goal of sufficient dispersion of the glue base and preliminary uniform fusion of the additives. Through analysis, the uniformity coefficient of the particle distribution image, the current fluctuation stabilization time, the stability of the torque in the dosing stage, and other indicators can be comprehensively evaluated, and a mixing uniformity factor can be calculated. If the factor is greater than or equal to a threshold value set by a person skilled in the art (such as 0.85, 0.9, etc., which is determined by experience or experiment), it is considered that the current parameter configuration is effective, i.e., it can be confirmed as the formal control parameter of the main glue base dosing stage and input into the mixer execution control system. This step ensures the rationality of the mixing parameters and the controllability of the mixing effect through a data closed-loop verification mechanism, effectively improving the self-adaptability of the system and the quality consistency control level.

[0105] Further, the preset adjustment scale refers to the step adjustment rule or parameter change range set for the optimization of the dosing mixing parameters, which is used for directional fine tuning when the mixing effect is not ideal, such as adjusting the stirring time by ±10 seconds, the rotating speed by ±5 rpm, and the stage proportion by ±5%. According to the preset adjustment scale, one or more variables (such as the stirring time, the segmented rhythm, and the feeding sequence) in the initial parameters are adjusted within a limited range, and a new set of stage dosing mixing parameters is generated. The parameters are used for a new mixing process again, and the mixing uniformity is analyzed again. If the mixing uniformity factor generated by the current parameters is greater than or equal to the threshold value, it means that the adjusted parameters are effective, i.e., they are confirmed as the formal control parameters of the main glue base dosing stage.

[0106] In order to facilitate a further understanding of the present application, the technical solutions of the present application will be described in detail in conjunction with preferred embodiments.

[0107] In step a1 of Embodiment 1, the following raw materials are weighed: ordinary Portland cement 250 g, fly ash 100 g, silica fume 30 g, floating bead 20 g, limestone powder 50 g, slag light sand (40-70) 200 g, slag light sand (70-140) 200 g, tailings sand (40-70) 100 g, waste rubber particles 20 g, redispersible latex powder (vinyl acetate / ethylene copolymer) 20 g, cellulose ether (HPMC) 3.0 g, calcium formate 5.0 g, polycarboxylic acid water reducer 2.0 g, wood fiber 2 g, starch ether 0.5 g, and air entraining agent 0.1 g.

[0108] In step a2 of Embodiment 1, the above-mentioned powder is prepared according to the production process of preparing dry powder, and is ready for use.

[0109] In step a3 of Embodiment 1, 290 g of water is sucked with a straw.

[0110] Step a4, add the powder to the liquid of step a3, prepared according to the above preparation method, to obtain the high-coated cement-based ceramic tile adhesive.

[0111] The performance indexes of the prepared high-coated cement-based ceramic tile adhesive are tested according to JGJ / T70 "Standard Test Methods for Basic Properties of Building Mortars" and JC / T547-2017 "Ceramic Tile Adhesives", and the test results are shown in Tables 1 and 2.

[0112] Example 2, step b1, weigh the following raw materials: Portland cement 300g, fly ash 30g, silica fume 20g, metakaolin 30g, floating beads 20g, stone powder 50g, slag light sand (40-70) 250g, slag light sand (70-140) 150g, tailings sand (40-70) 74g, expanded vitrified microbead 50g, redispersible latex powder (acrylate / styrene copolymer) 15g, cellulose ether (HEMC) 3.0g, calcium formate 2g, naphthalene water reducer 5.0g, wood fiber 1g, starch ether 0.2g, air entraining agent 0.07g.

[0113] Step b2, prepare the above powder according to the production process of preparing dry powder, for standby use;

[0114] Step b3, use a straw to suck 310g of water.

[0115] Step b4, add the powder of step b2 to the liquid of step b3, prepared according to the above preparation method, to obtain the high-coated cement-based ceramic tile adhesive.

[0116] The performance indexes of the prepared high-coated cement-based ceramic tile adhesive are tested according to JGJ / T70 "Standard Test Methods for Basic Properties of Building Mortars" and JC / T547-2017 "Ceramic Tile Adhesives", and the test results are shown in Tables 1 and 2.

[0117] Example 3, step c1, weigh the following raw materials: Portland cement 350g, silica fume 20g, floating beads 30g, heavy calcium 30g, slag light sand (40-70) 150g, slag light sand (70-140) 200g, tailings sand (40-70) 50g, polyhollow silica beads 100g, expanded vitrified microbead 50g, redispersible latex powder (vinyl acetate / ethylene copolymer) 10g, cellulose ether (HEC) 3g, melamine water reducer 3.0g, air entraining agent 0.05g.

[0118] Step c2, prepare the above powder according to the production process of preparing dry powder, for standby use;

[0119] Step c3, use a straw to suck 330g of water.

[0120] Step c4, the powder of step c2 is added into the liquid of step c3, prepared according to the above preparation method, to obtain a high-coated cement-based ceramic tile adhesive.

[0121] The performance indexes of the prepared high-coated cement-based ceramic tile adhesive are tested according to JGJ / T70 "Standard Test Methods for Basic Properties of Building Mortars" and JC / T547-2017 "Ceramic Tile Adhesives", and the test results are shown in Tables 1 and 2.

[0122] Step s1, the raw materials are weighed as follows: ordinary portland cement 350g, tailings sand (40-70) 634.5g, redispersible latex powder (vinyl acetate / ethylene copolymer) 12g, cellulose ether (HPMC) 3.0g, starch ether 0.5g.

[0123] Step s2, the above components are weighed according to the proportion, and after weighing, the cement, cellulose ether, redispersible latex powder, early strength agent, and starch ether are first put into a mixer and mixed for 15-30s, and then the heavy sand is put into the mixer and mixed for 30-60s. After mixing, bag packaging is performed for standby;

[0124] Step s3, 230g of water is sucked with a straw.

[0125] Step s4, the powder of step s2 is added into the liquid of step s3, prepared according to the above preparation method, to obtain a cement-based heavy ceramic tile adhesive.

[0126] The performance indexes of the prepared cement-based heavy ceramic tile adhesive are tested according to JGJ / T70 "Standard Test Methods for Basic Properties of Building Mortars" and JC / T547-2017 "Ceramic Tile Adhesives", and the test results are shown in Tables 1 and 2.

[0127] The performance is tested according to JGJ / T70 "Standard Test Methods for Basic Properties of Building Mortars", and the results are shown in Table 1.

[0128] Table 1 Test Data Table

[0129]

[0130] The performance is tested according to JC / T547-2017 "Ceramic Tile Adhesives", and the results are shown in Table 2.

[0131] Table 2 Test Data Table

[0132]

[0133] Having described various embodiments of the application, it is to be understood that the above description is meant to be illustrative only, and that many modifications and variations of the embodiments are possible without departing from the scope and spirit of the described embodiments. Many modifications and variations of the described embodiments are possible in light of the above teachings. It is, therefore, to be understood that within the scope of the appended claims and their equivalents, the described embodiments can be practiced otherwise than as specifically described.

Claims

1. A high coating rate cement-based tile adhesive, characterized in that: Calculated by mass percentage, it includes the following components: Cement 25.0% to 40.0%; Lightweight filler 10.0% to 25.0%; Heavy filler 0% to 8.0%; Light sand 0%~50.0%; Heavy sand 0% to 50.0%; Cellulose ether 0.20% to 0.40%; Early strength agent 0% to 0.40%; Water reducing agent 0.20% to 0.50%; Wood fiber 0% to 0.40%; Starch ether 0%~0.06%; Air entraining agent 0%~0.01%.

2. The high coating rate cement-based tile adhesive according to claim 1, characterized in that: The cement is at least one of general-purpose Portland cement and sulphoaluminate cement; Wherein, the lightweight filler is at least one of silica fume, high-density ore, fly ash, floating beads, and ecological sintering materials; The bulk density of the silica fume is 350 kg / m 3 ~450kg / m 3 ; The particle size of the high-altitude area is above 1000 mesh and the bulk density is 450kg / m 3 ~550kg / m 3 ; The bulk density of the fly ash is 800 kg / m 3 ~950kg / m 3 ; The particle size of the floating beads is 325 mesh, the sieve residue is less than 10%, and the bulk density is 600 kg / m 3 ~700kg / m 3 ; The fineness of the ecological sintering material is 45 microns, the sieve residue is ≤30.0%, and the bulk density is 800kg / m 3 ~900kg / m 3 .

3. The high coating rate cement-based tile adhesive according to claim 1, characterized in that: The heavy filler is at least one of heavy calcium, limestone powder, and stone powder; The particle size of the heavy calcium is 200 mesh and the bulk density is 1100 kg / m 3 ~1300kg / m 3 .

4. The high coating rate cement-based tile adhesive according to claim 1, characterized in that: The light sand is at least one of slag light sand, hollow silica beads, expanded vitrified microbeads, expanded perlite, expanded vermiculite, and waste rubber particles; The particle size range of the slag light sand is 40 mesh to 70 mesh, 70 mesh to 140 mesh, and the bulk density is 600 kg / m 3 ~800kg / m 3 , cylinder pressure strength 3.0MPa~10.0MPa; The particle size of the hollow silica beads ranges from 0.10 mm to 0.30 mm and 0.25 mm to 0.50 mm, and the bulk density is 300 kg / m 3 ~450kg / m 3 , cylinder pressure strength 2.0MPa~3.0MPa; Wherein, the heavy sand is at least one of natural sand and machine-made sand; The particle size range of the heavy sand is 40 mesh to 70 mesh, 70 mesh to 140 mesh, and the bulk density is 1200 kg / m 3 ~1400kg / m 3 ; The cellulose ether is at least one of HPMC, HEMC and HEC, and the viscosity of the cellulose ether is 15000 mPa·s to 100000 mPa·s.

5. The high coating rate cement-based tile adhesive according to claim 1, characterized in that: The early strength agent is a calcium salt series early strength agent, preferably calcium formate; Wherein, the water reducer is at least one of a polycarboxylate water reducer, a naphthalene-based water reducer, and a melamine water reducer; Wherein, the wood fiber is an organic flocculent fiber material obtained by chemical treatment and mechanical processing of natural renewable wood; The starch ether is hydroxymethyl starch and is a natural high molecular weight polyelectrolyte ether soluble in cold water.

6. The high coating rate cement-based tile adhesive according to claim 1, characterized in that: The air entraining agent is a structure-modified air entraining agent, which is obtained by compounding and modifying the air entraining agent with a modifier and a structure control agent, and the mass ratio of the modifier to the air entraining agent is 4-8:70-80; Wherein, the air entraining agent comprises at least one of sodium α-olefin sulfonate, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate; The modifier includes at least one of ethylenediaminetetraacetic acid, sodium citrate, silicone polyether emulsion, and hydroxyethyl cellulose; The structure regulating agent includes at least one of nano-silicon dioxide or montmorillonite.

7. A method for preparing a high-coverage cement-based tile adhesive according to any one of claims 1 to 6, characterized in that: include: Weigh each component according to the preset ratio to obtain a set of weighed component materials; The component materials are respectively placed in the feeding tank collection, and in the main adhesive base addition stage, the cement feeding tank, the light filler feeding tank, and the heavy filler feeding tank in the feeding tank collection are sequentially transferred to the mixer to add the component materials; In the preset monitoring window, the mixer is monitored for dosing and mixing based on the mixer monitoring sensor array, and the dosing and mixing parameters are optimized according to the monitoring results and the preset ratio to determine the dosing and mixing parameters for the main rubber base dosing stage; Feedback control is performed on the mixer based on the mixing parameters of the main gum base addition stage. After the main gum base addition stage is completed, the cellulose ether feeding tank, the wood fiber feeding tank, the starch ether feeding tank, the early strength agent feeding tank, the water reducing agent feeding tank, and the air entraining agent feeding tank in the feeding tank set are called up to add component materials in sequence according to dissolution kinetics, and the additive addition stage is monitored in combination with the mixer monitoring sensor array, and feedback control is performed on the mixer according to the monitoring results of the additive addition stage; After the additive addition stage is completed, the light sand feeding tank and the heavy sand feeding tank in the feeding tank set are called up to add the component materials to the mixer in sequence, and the aggregate uniform distribution stage is monitored in combination with the mixer monitoring sensor array, and the mixer is feedback controlled according to the monitoring results of the aggregate uniform distribution stage; When the aggregate uniform distribution stage is completed, a mixed cement-based tile adhesive with a high coating rate is obtained.

8. The method for preparing a high-coverage cement-based tile adhesive according to claim 7, wherein: In a preset monitoring window, the mixer is monitored for dosing and mixing based on the mixer monitoring sensor array, and dosing and mixing parameters are optimized according to the monitoring results and the preset ratio to determine the dosing and mixing parameters of the main rubber base dosing stage, wherein the dosing and mixing parameters of the main rubber base dosing stage include the dosing and mixing duration and the dosing and mixing speed in each stage, including: Extracting the mixer monitoring sensor array to perform dosing and mixing monitoring on the mixer to obtain a mixing monitoring data sequence, wherein each mixing monitoring data includes current, dosing speed, material weight and particle distribution uniformity; Performing iterative trend interactive analysis on the hybrid monitoring data sequence to determine hybrid monitoring iterative trend characteristics, and using the hybrid monitoring iterative trend characteristics as monitoring results; Identify the monitoring result and the preset ratio according to a preset dosing and mixing parameter identifier to determine the initial dosing and mixing parameters; A mixing balance analysis is performed on the initial addition mixing parameters. If the mixing balance factor is greater than or equal to a preset mixing balance factor threshold, the initial addition mixing parameters are used as the addition mixing parameters in the main glue base addition stage.

9. The method for preparing a high-coverage cement-based tile adhesive according to claim 8, wherein: Performing iterative trend interactive analysis on the hybrid monitoring data sequence to determine hybrid monitoring iterative trend characteristics, and using the hybrid monitoring iterative trend characteristics as monitoring results, including: performing trend analysis on the hybrid monitoring data sequence using a first interactive analysis branch and a second interactive analysis branch, respectively, to determine a first hybrid monitoring iterative trend feature and a second hybrid monitoring iterative trend feature, wherein the analysis scale of the first interactive analysis branch is greater than the analysis scale of the second interactive analysis branch; A similarity analysis is performed on the first hybrid monitoring iterative trend feature and the second hybrid monitoring iterative trend feature to construct an interaction matrix, and the first hybrid monitoring iterative trend feature is enhanced using the interaction matrix to obtain the hybrid monitoring iterative trend feature.

10. The method for preparing a cement-based tile adhesive with a high coating rate according to claim 8, wherein: If the mixing balance factor is less than the preset mixing balance factor threshold, the initial dosing mixing parameter is adjusted according to the preset adjustment scale to obtain the stage dosing mixing parameter. When the mixing balance factor of the stage dosing mixing parameter is greater than or equal to the preset mixing balance factor threshold, the stage dosing mixing parameter is used as the main glue base dosing stage dosing mixing parameter.

Citation Information

Patent Citations

  • Glass bead with honeycomb holes and tile glue with glass bead

    CN102633484A